Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pada Ompu Gende Coffee Medan - Riska Handayani; Adelina Lubis; Wan Suryani; Ihsan Effendi; Fitriani Tobing (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This study aims to determine "The Influence of Product Quality, Service Quality and Price on Consumer Satisfaction at "Ompu Gende Coffee Medan". This type of research is an associative and quantitative approach. The population in this study were consumers of Ompu Gende Coffee Medan as many as 170 customers using the slovin formula technique, so the number of samples in this study was 119 respondents taken from part of the population. Based on the test results, it can be seen that calculated on the Product Quality variable, it is obtained 4.320 where the table value at 5% which is 1.657 means positive. Quality of Service and Price of 2.251, 4.230 and 4.323 table of 1.657 with a probability of sig 0.05 on the variable Consumer Satisfaction. Based on the results of the F test, the calculated F value is 23,443 3.07 with Sig 0.000 0.05 indicating that Product Quality, Service Quality and Price simultaneously have a positive and significant effect on the Consumer Satisfaction variable. Adjusted R Square value obtained by 0.363 or 36.3% of Consumer Satisfaction can be explained by Service Quality and Trust, the remaining 63.7% is influenced by other factors not explained in this study.